Prevalence and Distribution of Diffuse Idiopathic Skeletal Hyperostosis on Whole-spine Computed Tomography in Patients With Cervical Ossification of the Posterior Longitudinal Ligament: A Multicenter Study. Issue 9 (November 2018) - Nishimura, Soraya; Nagoshi, Narihito; Iwanami, Akio; Takeuchi, Ayano; Hirai, Takashi; Yoshii, Toshitaka; Takeuchi, Kazuhiro; Mori, Kanji; Yamada, Tsuyoshi; Seki, Shoji; Tsuji, Takashi; Fujiyoshi, Kanehiro; et al.
Abstract : Study Design: This was a retrospective multicenter study. Objective: To clarify the progression of diffuse idiopathic skeletal hyperostosis (DISH) using whole-spine computed tomography in patients with cervical ossification of the posterior longitudinal ligament (OPLL). Summary of Background Data: DISH and cervical OPLL frequently coexist, and can cause ankylosing spinal fractures due to biomechanical changes and fragility of the affected vertebrae. The epidemiology and pathophysiology of DISH occurring with cervical OPLL are unclear. Materials and Methods: We used whole-spine computed tomography to determine the prevalence of DISH in 234 patients with a diagnosis of cervical OPLL based on plain cervical radiographs. We established a novel system for grading the progression of DISH based on a cluster analysis of the DISH distribution along the spine. We calculated the correlation coefficient between this grading system and patient age. Results: The prevalence of DISH in patients with cervical OPLL was 48.7%. Patients with DISH were significantly older than those who did not have DISH (67.3 vs. 63.4 y; P =0.005). Cluster analysis classified the DISH distribution into 6 regions, based on the levels affected: C2–C5, C3–T1, C6–T5, T3–10, T8–L2, and T12–S1. DISH was observed most frequently at T3–T10. We defined a system for grading DISH progression based on the number of regions involved, from grade 0 to 6. DISH was distributed at T3–T10 in >60% of the grade 1 patients, whereas most patients with DISH at the cervical or lumbar spine were grade 4 or 5. There was a weak but significant correlation between the DISH grade and patient age. Conclusions: DISH was present in nearly half of the patients with cervical OPLL. DISH was more common in older patients. DISH developed at the thoracic level and progressed into the cervical and/or lumbar spine with age. Level of Evidence: Level III.